Combination With Low-dose Dextromethorphan Improves the Effect of Amlodipine Monotherapy in Clinical Hypertension: A First-in-human, Concept-proven, Prospective, Dose-escalation, Multicenter Study. Issue 12 (March 2016) - Yin, Wei-Hsian; Chen, Pei; Yeh, Hung-I; Wang, Kuo-Yang; Hung, Yi-Jen; Tseng, Wei-Kung; Wen, Ming-Shien; Wu, Tao-Cheng; Wu, Chau-Chung; Cheng, Shu-Meng; Chen, Jaw-Wen
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The combination of low rather than high dose of dextromethorphan (DXM) with amlodipine (AM) could improve blood pressure (BP) reduction in hypertensive animals. The study aimed to evaluate the feasibility of different doses of DXM combined with standard AM treatment in clinical hypertension. This was a prospective, 14-week, dose-escalation, multicenter study. After 2-week run-in period with AM 5 mg/day, hypertensive patients who got the BP goal of 140/90 mmHg kept receiving AM monotherapy for another 12 weeks. The nonresponders, while kept on AM 5 mg/day, received additional DXM treatment for 3 sequential dose-titrated periods with initially 2.5 mg/day, followed by 7.5 mg/day, and finally 30 mg/day. Each period was for 4 weeks. The patients at BP goal after each treatment period were defined as the responders and kept on the same combination till the end of the study. The responder rate of each treatment period was recorded. The changes of BP and serum antioxidant/endothelial markers between week 14 and week 2 were evaluated. Of the 103 patients initially enrolled, 89 entered the treatment period. In the 78 patients completing the study, 31 (40%) at BP goal after 2-week AM run-in kept on AM monotherapy (DXM0). The addition of 2.5 (DXM2.5) and 7.5 mg/day (DXM7.5) of DXM enabled BP goal achievement in 22 (47%) nonresponders to AM monotherapy including 16 (29%) with DXM2.5 and 6 (18%) with DXM7.5. Only 4 patients (16%) reached BP goal with the combination of DXM 30 mg/day (DXM30). Overall, 73% of the 78 patients reached BP goal at the end of the 14-week study. Mean systolic BP was reduced by 7.9% ± 7.0% with DXM2.5 ( P  < 0.001) and by 5.4% ± 2.4% with DXM7.5 ( P  = 0.003) respectively at week 14 from that at week 2, which was unchanged in either DXM0 or DXM30 group. Besides, the effects of combination treatment were particularly significant in the patients with impaired endothelial function suggested by reduced serum NOx level at baseline. Accordingly, the combination with low dose of DXM was feasible to improve BP control in patients who failed to achieve the BP goal by standard AM monotherapy. The benefit effects might be significant especially in patients with impaired endothelial function.